2020
DOI: 10.1038/s41598-020-70856-8
|View full text |Cite|
|
Sign up to set email alerts
|

Perceived match between own and observed models’ bodies: influence of face, viewpoints, and body size

Abstract: People are generally unable to accurately determine their own body measurements and to translate this knowledge to identifying a model/avatar that best represents their own body. This inability has not only been related to health problems (e.g. anorexia nervosa), but has important practical implications as well (e.g. online retail). Here we aimed to investigate the influence of three basic visual features—face presence, amount of viewpoints, and observed model size—on the perceived match between own and observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 90 publications
2
10
0
Order By: Relevance
“…Based on this research, we hypothesized that own concrete and ideal body representations would show a stronger relationship than own concrete and own abstract body representations. Furthermore, in line with research that has shown that body size/shape estimation is affected by bodily self-esteem 26 , personality traits 61 , and body (dis)satisfaction with certain body parts 42 , 64 , we hypothesized that body estimation in the current study would be influenced by these psychological differences.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Based on this research, we hypothesized that own concrete and ideal body representations would show a stronger relationship than own concrete and own abstract body representations. Furthermore, in line with research that has shown that body size/shape estimation is affected by bodily self-esteem 26 , personality traits 61 , and body (dis)satisfaction with certain body parts 42 , 64 , we hypothesized that body estimation in the current study would be influenced by these psychological differences.…”
Section: Introductionmentioning
confidence: 61%
“…own concrete body representation), using a data-driven method measuring implicit offline body representations for the first time. We hypothesized that framing own body estimation in a practical context would increase the relationship between perceived body measurements based on implicit offline body representations and real own body measurements, contrary to the absence of such a relationship when no such context is provided 26 or when this relationship is measured explicitly 61 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, while we are used to experience our own body in movement, movement dynamics have thus far not been included when investigating own-perceived body matching, although action and motor experience have been shown to be important in the development and maintenance of body ownership (e.g., Dummer et al, 2009 ; Nava et al, 2018 ). Second, the avatar/model bodies during own-perceived body matching are usually presented either without clothing (e.g., De Coster et al, 2020 ) or with static clothing that does not provide additional cues (e.g., wrapping of different sizes of clothing around the body, movement of clothing when body moves) for body size estimation (e.g., Cornelissen et al, 2017 ; Mölbert et al, 2018 ; Thaler et al, 2018 ; Sadibolova et al, 2019 ). While it has been shown that dynamics play an important role in the perception of clothing ( Aliaga et al, 2015 ) and that observers are able to infer certain body properties (e.g., body stiffness) from clothing dynamics ( Romero et al, 2020 ), as well as the clothing’s mechanical properties ( Bi and Xiao, 2016 ), the question whether body size can be predicted by these dynamics and whether own-perceived body matching would be improved by these additional cues remain open questions.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, we expected them to show a preference for smaller- compared to bigger-sized avatars, irrespective of their own body size. Importantly, we contextualized the task of matching own and perceived body in a real-life situation by (1) comparing the accuracy of matching participants’ own with a perceived avatar’s body that was either static or dynamic (walking avatar), (2) fitting the observed model/avatar with a computer-simulated dress in different sizes, and (3) specifically asking participants about their wish to use the perceived model/avatar for online shopping ( De Coster et al, 2020 ). Concerning the effect of movement dynamics, we hypothesized that the addition of dynamic movement cues would increase participants’ ability to accurately determine their own body size/shape given the additional information that these movement cues provide and the resemblance to our everyday real-life environment.…”
Section: Introductionmentioning
confidence: 99%